Strategies and Challenges in Teaching English in English Courses - Nadia Putri Nuraini; Feisal Aziez; Santhy Hawanti (UM Purwokerto Press, 2024)
English courses are part of non-formal education conducted outside formal education, and the curriculum and methodology can be adjusted. This research investigates what strategies teachers use and what challenges teachers face when teaching English in English courses. This qualitative research involved two teachers from two different English courses. This research uses in-depth interviews and thematic analysis to collect data. The research found that the challenges faced when teaching English in non-formal education were student diversity, student mood, and accommodating students' needs. Then, the strategies teachers use during the learning process are observation, personal approaches to students, simplifying teaching materials, establishing prior agreements, and creating lesson plans. This research contributes to the existing literature by providing insights into effective teaching strategies and identifying key challenges in English course settings.